The impact of human resource management practices on employee creativity in Sharjah Police in the United Arab Emirates (UAE) - Alhosani, Faisal Ismail Sayed Ali (2022)
Human resource management practices are considered to be an essential component in achieving positive work outcomes and individual effectiveness. Many of the previous studies have explored the role of psycho-social factors in explaining employee creativity. However, the role of individual factors in enhancing employee creativity has gained little attention in this research area. The main objective of this study is to investigate the impacts of human resource management practices in improving employee creativity in the Sharjah Police, United Arab Emirates (UAE). This is achieved by testing the effect of employee communication, employee development, rewards and recognition as independent variables on the organization’s employee creativity. This quantitative research study benefited from a statistical evaluation that is based on detailed solutions and techniques of variance and covariance, correlation and regression. This study focuses on the Sharjah Police in the United Arab Emirates, albeit there are previous studies on a similar subject but are departing from the scope of this study. To assess the role of HRM practices in improving employee creativity, a set of questionnaires were created and modified from various literary works to suit the needs of this study. The population for this assessment encompasses the employees of the Sharjah Police in the United Arab Emirates. The targeted sample size is 367, with 307 representing the valid data set. The findings of this study show the main dependent variable of employee creativity demonstrates satisfactory predictive power and significant predictive factor. The proposed model explains 96.2% of the variances in the spelling score of employee creativity in the business sector institutions in the UAE are significantly associated with the independent variables of employee communication, employee development, rewards and recognition.